Antifouling Ability of Hydrophilic PVDF-TiO2 membrane Evaluated by Critical Flux and Threshold Flux - Xie Wanying; Li Ji; Sun Feiyun; Dong Wenyi (E3S Web of Conferences, 2020)
The PVDF flat-membrane was modified by hydrophilic nano-TiO2, which blending by ultrasonication and mechanical stirring pretreatment in phase inversion method. To evaluate the permeate productivity and anti-fouling capacity of protein solution, both the critical flux (JCW) and threshold flux (JTH) of PVDF and PVDF-TiO2 membrane were firstly measured by Advanced Constant Pressure-step Method in cross-flow filtration apparatus. Some evaluation indicators were utilized to analyze the results, such as Flux vs. Time and TMP vs. Time Curves, flux decline rate (dFlux/dt) and TMP-Fluxave curve. Two type fluxes were compared, results exhibited that hydrophilic PVDF-TiO2 modified membrane possessed a higher level of both Jcw and JTH and better anti-protein fouling ability after testing by Advanced Constant Pressure-step Method.